2017
DOI: 10.1200/jgo.2015.002527
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban: An Affordable and Effective Alternative in Cancer-Related Thrombosis?

Abstract: BackgroundVenous thromboembolic events (VTEs) are common and potentially fatal complications in cancer patients, and they are responsible for the second most common cause of death. Low molecular weight heparin (LMWH) is the gold-standard treatment, but the costs involved limit its use, especially in developing countries. Recently, the oral anticoagulant rivaroxaban, which directly inhibits factor Xa, was approved for VTE treatment.MethodsWe conducted a retrospective analysis from January 2009 to February 2014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, several small studies corroborate the perceived benefits of rivaroxaban over LMWHs in patients with cancer. A retrospective analysis of electronic medical records for cancer patients with VTE reported that rivaroxaban had similar safety (absence of bleeding) and efficacy (rethrombosis) when compared to a LMWH plus warfarin ( P = .54 and P = .25, respectively) or to LMWH alone ( P = .46 and P = .29, respectively) . A separate prospective cohort study assessed rivaroxaban in 200 patients with cancer‐associated thrombosis and reported 6‐month cumulative incidence rates of 4.4% for new and recurrent VTEs and 2.2% for major bleeding .…”
Section: Discussionmentioning
confidence: 99%
“…However, several small studies corroborate the perceived benefits of rivaroxaban over LMWHs in patients with cancer. A retrospective analysis of electronic medical records for cancer patients with VTE reported that rivaroxaban had similar safety (absence of bleeding) and efficacy (rethrombosis) when compared to a LMWH plus warfarin ( P = .54 and P = .25, respectively) or to LMWH alone ( P = .46 and P = .29, respectively) . A separate prospective cohort study assessed rivaroxaban in 200 patients with cancer‐associated thrombosis and reported 6‐month cumulative incidence rates of 4.4% for new and recurrent VTEs and 2.2% for major bleeding .…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated that rivaroxaban was not inferior to LMWH in terms of recurrence, bleeding incidence, or mortality. However, patients with GI tract cancer accounted for only 25.4%–60% of patients in these studies 13151740. Therefore, these results cannot be generalized to the GI tract cancer population.…”
Section: Discussionmentioning
confidence: 79%
“…The inclusion and exclusion of citations/articles identified through the systematic literature search are illustrated in Figure . A total of six studies evaluating rivaroxaban for the treatment of CAT and published between 2016 and 2017 were included in the analysis (Table ) . Of the six studies, three were prospective (one multicenter) and three were retrospective (one used administrative claims data).…”
Section: Resultsmentioning
confidence: 99%
“…A total of six studies evaluating rivaroxaban for the treatment of CAT and published between 2016 and 2017 were included in the analysis (Table 1). [16][17][18][19][20][21] Of the six studies, three were prospective (one multicenter) and three were retrospective (one used administrative claims data). Individual study sample sizes ranged from 41 to 949 patients.…”
Section: Resultsmentioning
confidence: 99%